Antibacterial Activity Test Of Ethanol Extract Of Dadap Serep Leaves (Erythrina Lithosperma Miq) Against The Growth OF Escherichia Coli - Amelia Niwele; Alice M. Cl. Luhulima; Ananda Dwiyanti Hataul (Jurnal EduHealth, 2024)
Dadap serep leaves (Erythrina lithosperma Miq) are one type of important medicinal plant that is widely used in traditional medicine. This dadap serep leaf plant can be used as a medicine for fever, to facilitate breast milk, stomach ache, diarrhea, and to prevent miscarriage. The chemical compounds contained in dadap serep leaves which function as antibacterial compounds are flavonoids. Escherichia coli bacteria are gram-negative bacteria, and are facultative anaerobes. This study aims to determine the antibacterial activity of dadap serep (Erythrina lithosperma Miq) leaf extract which was dissolved using 70% ethanol solvent. The type of research. The phytochemical screening test uses the maceration method and for the antibacterial activity test uses the agar diffusion method. The results of research conducted on phytochemical screening tests were the content of secondary metabolite compounds in dadap serep leaves, namely saponins, tannins, flavonoids and alkaloids. And the results of research carried out on testing the antibacterial activity of ethanol extract of dadap serep leaves (Erythrina lithosperma Miq) on the growth of Escherichia coli bacteria at concentrations of 5%, 10% and 20%. With an average inhibition zone at a concentration of 5% 10.36 mm, 10% 11.8 mm, and 20% 13.13 mm. Cotrimoxazole as a positive control has an inhibition zone of 20.53 mm, and distilled water as a negative control does not have an inhibition zone.